LABORATORY MEASUREMENTS OF SUBSYNCHRONOUS RESONANCE. - Limebeer, D; Harley, R; Lahoud, M; Nattrass, H (IFAC (IFAC Proc Ser) by Pergamon Press, 1980)
Results obtained from a laboratory system specially designed to investigate subsynchronous resonance are reported. This laboratory system was designed to model as closely as possible the new nuclear powered turbogenerators to be installed at Koeberg power station in South Africa. In the case of some of the laboratory measurements, equivalent theoretical results are presented in order to test the validity of the mathematical models currently being employed. The theory describing the system dynamics and some of the features of the laboratory system are presented.